2016
DOI: 10.1038/ncomms11036
|View full text |Cite
|
Sign up to set email alerts
|

Cellular forces and matrix assembly coordinate fibrous tissue repair

Abstract: Planar in vitro models have been invaluable tools to identify the mechanical basis of wound closure. Although these models may recapitulate closure dynamics of epithelial cell sheets, they fail to capture how a wounded fibrous tissue rebuilds its 3D architecture. Here we develop a 3D biomimetic model for soft tissue repair and demonstrate that fibroblasts ensconced in a collagen matrix rapidly close microsurgically induced defects within 24 h. Traction force microscopy and time-lapse imaging reveal that closur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 43 publications
7
129
1
Order By: Relevance
“…During contraction of the collagen gels by fibroblasts, cells accumulate at the microtissue surface (S1 and S2 Figs), in agreement with previous observations [10,13]. Using fibronectin knockout (Fn -/- ) versus floxed mouse fibroblasts (Fn f/f ), we found that fibronectin plays a crucial role in directing the accumulation of cells at the tissue surface (Fig 2).…”
Section: Discussionsupporting
confidence: 91%
“…During contraction of the collagen gels by fibroblasts, cells accumulate at the microtissue surface (S1 and S2 Figs), in agreement with previous observations [10,13]. Using fibronectin knockout (Fn -/- ) versus floxed mouse fibroblasts (Fn f/f ), we found that fibronectin plays a crucial role in directing the accumulation of cells at the tissue surface (Fig 2).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the myosin-dependent contraction and migration of fibroblasts around a wound gap are primary mechanisms through which closure occurs, as opposed to the proliferation of cells [23]. The forces transmitted through cell-cell contacts have proven to be critical factors in layers of cells moving together, as in wound healing [24].…”
Section: Matrix Malleability and Reorganization By Stem Cellsmentioning
confidence: 99%
“…The cells compact the collagen gel, forming 3D tissues suspended between multiple cantilevers. By monitoring changes in cantilever deflection, one can calculate the tension generated by the tissue during processes such as 3D wound healing [137]. These tissues have been especially useful for investigating relationships between physical forces generated by a tissue and ECM protein deposition and remodeling [135137].…”
Section: Designing Microfabricated Tissues To Study Traction Forcesmentioning
confidence: 99%